Impact of Coronavirus on Stock Market - Reepu; Sharma, Ritu; Chadha, Ashita (The journal of contemporary issues in business and government, 2021)
The world has been suffering from Corona pandemic called as COVID-19. It has spread to more than 170 nations with the death toll being massive. Several thousand people have also recovered. Many pharmaceutical companies are testing to develop medicines and vaccines to cure the disease, but success has not been achieved yet. Wuhan of China reported about it in December and today four month later life has started to revert to normalcy there but the world is gripped under curfews, lock-down which has brought financial slowdown and crippled economic growth. Stock markets are also not devoid of its impact. Different nations have extended help to each other but yet the overall impact of COVID-19 is immeasurable. The present paper is an attempt to study the impact of COVID-19 on stock exchanges across the world. The implication of this study is that the managers may think to provide a solution in this tumultuous situation.